PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PT. SEBANG GLOBAL TOUR INDONESIA - Aris Budiono; Tumiyati (LPPM Universitas Asa Indonesia, 2018)
This study aims to determine the effect of service quality, brand image and trust in the loyalty of PT.Sebang Global Tour Indonesia customers. In this study, the authors conducted a survey by distributing questionnaires to customers of PT. Sebang Global Tour Indonesia. The number of samples in this study was 100 customers obtained by using random non-random sampling technique, where the respondents who were sampled were customers who were willing to fill out the questionnaire. After conducting questionnaires. For the descriptive analysis method, the writer uses percentage and average analysts. To test the effect of service quality, brand image and trust, the author uses multiple linear regression analysis with F test and T test. The results of the study show both variables jointly affect the customer loyalty of PT. Sebang Global Tour Indonesia. By using the T test, it was found that service quality had a significant effect on increasing customer loyalty at PT. Sebang Global Tour Indonesia is 7,698%, while brand image also influences customer loyalty at PT. Sebang Global Tour Indonesia. The ability of the brand image variable to explain customer loyalty is 13.214% and trust also affects customer loyalty at PT. Sebang Global Tour Indonesia. The ability of the trust variable to explain customer loyalty is 9.980%. The contribution of the independent variable to the Customer Loyalty of PT. Sebang Global Tour Indonesia is 53.144%, while the remaining 46.86 is influenced by other variables not included in the model or not examined.